Analisis Determinan Volume Impor Gandum di Indonesia - Ni Putu Kania Putri; Ni Luh Karmini (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Wheat is one of the food commodities consumed by the Indonesian people. The need for wheat in Indonesia from year to year tends to increase but is almost entirely met through imports and makes Indonesia one of the world's largest wheat importers. Dependence on food commodities from the import side has a huge risk for national food security because in addition to the increasingly limited foreign exchange owned, there is also uncertainty in terms of quantity and price. The purpose of this study is to find out the factors that affect wheat imports in Indonesia. The variables in this study are foreign exchange reserves, international wheat prices, domestic rice prices, and the US dollar exchange rate. This study uses secondary data with a quantitative approach using 34 data. Data analysis techniques using descriptive statistical analysis and multiple linear regression analysis. The results of this study show 1) Foreign Exchange Reserves, International Wheat Prices, Domestic Rice Prices, and the US Dollar Exchange Rate simultaneously have a positive and significant effect on the Volume of Wheat Imports in Indonesia, 2) Foreign Exchange Reserves partially have a positive and significant effect on the Volume of Wheat Imports in Indonesia, 3) International Wheat Prices partially have a negative and significant effect on the Volume of Wheat Imports in Indonesia, 4) Domestic Rice Prices and the US Dollar Exchange Rate have no significant effect on the Volume of Wheat Imports in Indonesia.